A portfolio analysis of industrial structure - Frank G. Barry; Colm Kearney (University College Dublin, Department of Economics, 2003)
Industrial sectors producing income-elastic products can grow rapidly but are highly vulnerable to fluctuations in the world economy. Policymakers need to take into account this trade-off between output and employment growth over the longer term and volatility in the short to medium term. We bring the principles of portfolio theory to bear on the issue. Our analysis is applied to Irish manufacturing employment where growth has been concentrated in foreign-owned sectors such as Office and Data Processing Equipment, Pharmaceuticals and Professional Instruments. We show that, increased volatility notwithstanding, the country's hightech FDI-driven strategy has brought the economy's industrial portfolio closer to the mean-variance efficiency frontier.
hdl:10197/1262
Keywords: O21; R30; G11; 330; Industrial Structure; Portfolio Analysis; Industriestruktur; Internationale Arbeitsteilung; Exportdiversifizierung; Industrielle Beschäftigung; Irland